Formação leitora de estudantes da EJA por meio da literatura de cordel - Marilene Sacramento Miranda (2023)
This study presents a thoughtfulness on the reading training process of the students from the Andragogical Youth and Adult Education (EJA), during the fulfillment of this investigation at the Public State Education Institution: “Colégio Estadual Luiz Viana Filho (CELVF)”, located at the city of Candeias-BA, through the Cordel Literature. This study aimed to identify which actions can be developed to increase the students who participated of this research reading capacity, so they can continue to read day after day and keep up on their groundwork. For that reason, the autoethnographic methodological procedure was used because it allowed me to observe how the study of my individual self could contribute to relevant questions to a whole collectivity, and vice versa. At the same time, carry the experience of studying the reading training process of students and (self) training of the professor-researcher considering the personal, cultural, and social story of the participants in this scrutiny and specific conditions in which teaching-learning of reading occurs. These were the factors that led me to choose Cordel Literature. Another factor that contributed to my personal choice was the fact that it is a textual genre that presents definition, histories, and cultures and the potential to compose an aesthetic experience in which students can identify themselves with. Moreover, it admitted the presence of many student’s voices, that pervades the texting creating, participating as “Cordealistas” as well. The purpose of this study is to discuss the relevance of Cordel Literature at school, once and since it is considered as Art. The participants have had the opportunity to read and create, and to become authors of Cordel texts, enhancing their reading and creative skills through exquisite livings at reading and creating workshops, which led to the pedagogical product of this research.